PENGARUH LEVERAGE & SALES GROWTH TERHADAP FINANCIAL DISTRESS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Azari, Refina; Tjakrawala, F.X. Kurniawan (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The research was conducted to find out how leverage and sales growth play a role in financial distress, in the manufacturing industry listed on the IDX during the 2015-2019 period. The sample was obtained using certain criteria by purposive sampling using statistical software assistance in the form of SPSS version 21 with logistic regression analysis. Research proves that Debt asset to ratio (DAR) is able to have a significant effect on financial distress, Sales growth (SG) does not have a significant effect on financial distress. The moderating variable used is profitability, profitability proxied by return on assets (ROA) is able to significantly weaken the effect of leverage on the interest coverage ratio (ICR) and profitability is able to significantly weaken the relationship between sales growth and interest coverage ratio (ICR). The implications of this research are the need to increase the effectiveness of the company's management role in taking actions that can affect financial conditions in preventing financial difficulties.